The impact of funding models on the integration of Ontario midwives: a qualitative study - Elizabeth K. Darling; Sylvie B. Lemay; 'Remi Ejiwunmi; Katherine J. Miller; Ann E. Sprague; Rohan D'Souza (BMC, 2023)
Abstract Background Nearly 30 years post legalisation and introduction, midwifery is still not optimally integrated within the health system of Canada's largest province, Ontario. Funding models have been identified as one of the main barriers. Methods Using a constructivist perspective, we conducted a qualitative descriptive study to examine how antepartum, intrapartum, and postpartum funding arrangements in Ontario impact midwifery integration. We conceptualized optimal 'integration' as circumstances in which midwives' knowledge, skills, and model of care are broadly respected and fully utilized, interprofessional collaboration and referral support the best possible care for patients, and midwives feel a sense of belonging within hospitals and the greater health system. We collected data through semi-structured telephone interviews with midwives, obstetricians, family physicians, and nurses. The data was examined using thematic analysis. Results We interviewed 20 participants, including 5 obstetricians, 5 family physicians, 5 midwives, 4 nurses, and 1 policy expert. We found that while course-of-care-based midwifery funding is perceived to support high levels of midwifery client satisfaction and excellent clinical outcomes, it lacks flexibility. This limits opportunities for interprofessional collaboration and for midwives to use their knowledge and skills to respond to health system gaps. The physician fee-for-service funding model creates competition for births, has unintended consequences that limit midwives' scope and access to hospital privileges, and fails to appropriately compensate physician consultants, particularly as midwifery volumes grow. Siloing of midwifery funding from hospital funding further restricts innovative contributions from midwives to respond to community healthcare needs. Conclusions Significant policy changes, such as adequate remuneration for consultants, possibly including salary-based physician funding; flexibility to compensate midwives for care beyond the existing course of care model; and a clearly articulated health human resource plan for sexual and reproductive care are needed to improve midwifery integration.